Core needle biopsy versus incisional biopsy for differentiation of soft-tissue sarcomas: a systematic review and meta-analysis - Birgin, Emrullah; Yang, Cui; Hetjens, Svetlana; Reißfelder, Christoph; Hohenberger, Peter; Rahbari, Nuh Nabi (Cancer, 2020)
Background Controversies exist regarding the biopsy technique of choice for the accurate diagnosis of soft-tissue sarcoma (STS). The objective of this systematic review and meta-analysis was to compare the diagnostic accuracy of core needle biopsy (CNB) versus incisional biopsy (IB) in STS with reference to the final histopathological result. Methods Studies regarding the diagnostic accuracy of CNB and IB in detecting STS were searched systematically in the MEDLINE and EMBASE databases. Estimates of sensitivity and specificity with associated 95% CIs for diagnostic accuracy were calculated. The risk of bias was assessed using the Quality Assessment of Diagnostic Accuracy Studies version 2 (QUADAS-2). Results A total of 17 studies comprising 2680 patients who underwent 1582 CNBs and 241 IBs with subsequent tumor resection met the inclusion criteria. The sensitivity and specificity of CNB and IB to detect the dignity of lesions were 97% (95% CI, 95%-98%) and 99% (95% CI, 97%-99%), respectively, and 96% (95% CI, 92%-99%) and 100% (95% CI, 94%-100%), respectively. Estimates of the sensitivity and specificity of CNB and IB to detect the STS histotype were 88% (95% CI, 86%-90%) and 77% (95% CI, 72%-81%), respectively, and 93% (95% CI, 87%-97%) and 65% (95% CI, 49%-78%), respectively. Patients who underwent CNB had a significantly reduced risk of complications compared with patients who underwent IB (risk ratio, 0.14; 95% CI, 0.03-0.56 [P ≤ .01). Quality assessment of studies revealed a high risk of bias. Conclusions CNB has high accuracy in diagnosing the dignity of lesions and STS histotype in patients with suspected STS with fewer complications compared with IB. Therefore, CNB should be regarded as the primary biopsy technique.
Gesehen am 17.08.2021